PENGARUH CORPORATE RISK, CAPITAL INTENSITY DAN INVENTORY INTENSITY TERHADAP AGRESIVITAS PAJAK - Damaris Marpaung (PT Sanagi Edu Konsultan, 2025)
This study aims to examine the effect of corporate risk, capital intensity and inventory intensity on tax aggressiveness in health sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. Sampling in this study using purposive sampling technique so that 40 research samples were obtained. This research uses quantitative methods with secondary data obtained from the website www.idx.co.id. The analysis technique used in this research is multiple linear regression analysis using SPSS. Based on the results of multiple linear regression analysis with a significance level of 5%, it is concluded that corporate risk and capital intensity have no influence on tax aggressiveness. While inventory intensity has a positive influence on tax aggressiveness. And simultaneously corporate risk, capital intensity and inventory intensity have a positive effect on tax aggressiveness.